Effects of differents bandwidths knowledge of results on the acquisition of a serial motor skill - M. Colen; M. Zubiaur (Asociación Española de Ciencias del Deporte, 2010)
The aim of this study was to investigate the effects of three different ranks of bandwidth KR in the learning of a serial motor task. The participants were 45 undergraduate students, of both genders, randomly assigned to tree groups: (1) wide bandwidth was 10% of the total time; (2) narrow bandwidth was 5% of the total time, and (3) precision of error (BW.0) where the bandwidth was 0%.. The serial task consisted on putting a tennis ball respecting a previously determined time in six holes made on a wooden platform. The experiment was done in three phases, acquisition, immediate retention and retention delayed 24 hours after the acquisition test. The statistical analysis did not point out differences among the three groups regarding precision and consistency at any phases. I spite of not seen significant differences among the ranks, we concluded that the design of bandwidth KR is beneficial for a serial task motor learning and the utilization of bandwidth KR is positive for learning, but can present short-term effects, since long time limits on improvements of performance were not verified. On the other hand we encourage further studies designs that combine other ranks of KR with other variables, and using more complex tasks on the attempt of obtaining more significant results relating to the influence of the bandwidth KR in the motor learning.  Key Words: Motor learning; Knowledge of results; Bandwidth